ANALISIS BERPIKIR KREATIF SISWA MTS DALAM MENYELESAIKAN MASALAH OPEN-ENDED DITINJAU DARI GENDER DAN SELF-CONCEPT MATEMATIS - Robi'atul Bangka Wiyah, - (2022)
This study aims to describe the creative thinking abilities of male and female students who have high, moderate, and low mathematical self-concepts in solving open-ended problems. This qualitative research with a case study was conducted in one of the MTs in the Bangka Regency. The subjects were nine students of grade VIII who had received learning about social arithmetic. The data was collected through a mathematical self-concept questionnaire, creative thinking test about open-ended problems, and interviews. The results showed there (1) the creative thinking skills of male and female students who have high mathematical self-concepts are two male students classified as "very creative" and "less creative" and two female students classified as "very creative" and "quite creative", (2) the creative thinking skills of male and female students who have moderate mathematical self-concepts are two male students are classified as "less creative" dan "not creative" and two female students classified as "not creative" and (3) there are no female students who have low mathematical self-concept, while one male student who have low mathematical self-concepts classified as "not creative".